Pisando las huellas de Luis Lobera de Ávila: de un Banquete a un Vergel. - BALDISSERA, ANDREA (Scripta)
The study tries to establish the relationships between the Banquete de nobles caballeros (1530) and the Vergel de Sanidad (1542) by Luis Lobera de Ávila, as inescapable premise to define the textual characters of two important documents in the history of the lexicon of Hispanic food. Both some features of the enlargement represented by the Vergel and the relationships between discourse in Spanish and marginal glosses in Latin are investigated.